2013
DOI: 10.1002/dc.23018
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic vacuoles: Clue in the fine‐needle aspiration diagnosis of melanoma

Abstract: For the fine-needle aspiration (FNA) diagnosis of melanoma recognition of characteristic morphologic features is key. In our practice we noted that cytoplasmic vacuoles in Romanowsky-stained FNA smears of melanoma appeared to be a frequent finding. To investigate this premise, we examined 36 consecutive melanoma FNA cases that had both adequate Papanicolaou-stained and Romanowsky-stained smears in an effort to determine the prevalence, and thereby, the potential diagnostic utility of cytoplasmic vacuoles in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Multinucleation is a frequent feature, with some series suggesting their presence in 100% of cases. 15 The presence of multinucleated tumor cells showed no predilection by site aspirated but was statistically more likely in aspirates where the predominant cell type was epithelioid over spindled (Fig. 9).…”
Section: Nuclear Features and Placementmentioning
confidence: 94%
See 3 more Smart Citations
“…Multinucleation is a frequent feature, with some series suggesting their presence in 100% of cases. 15 The presence of multinucleated tumor cells showed no predilection by site aspirated but was statistically more likely in aspirates where the predominant cell type was epithelioid over spindled (Fig. 9).…”
Section: Nuclear Features and Placementmentioning
confidence: 94%
“…15,25 In the study by Chen et al, 15 cytoplasmic vacuoles were found in 83% of cases, all on air-dried smears, regardless the cell types. The potential origin of these vacuoles has been investigated with electron microscopy.…”
Section: Cell Shape and Cytoplasmic Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…Malignant melanoma metastases are frequently diagnosed by FNA cytology . The diagnosis is usually relatively straightforward when the aspirates show abundant cellularity with predominance of single tumor cells with obvious cytologic features of malignancy, prominent macronucleoli, binucleation, nuclear eccentricity, and nuclear pseudoinclusions.…”
mentioning
confidence: 99%